2009
DOI: 10.1002/uog.6428
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated insulin‐like growth factor binding protein‐1 in cervical secretions and sonographic cervical length in the prediction of spontaneous preterm delivery

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…14 Therefore, sonographically measured cervical length of >25mm with a negative phIGFBP-1 test in a symptomatic patient indicates a low risk of preterm delivery and may therefore allow avoidance of unnecessary therapies. 15 NPV for predicting the risk of pre-term delivery was increased on combining FFN assessment to cervical length measurements in present study also ( Table 3) similar to that of Audibert F et al 8 In asymptomatic high risk group both FFN and phIGFBP-1 tests were found to have poor sensitivity and PPV; however NPV of the tests were high. Cervical length in this group also had poor accuracy to predict preterm birth.…”
Section: Discussionsupporting
confidence: 85%
“…14 Therefore, sonographically measured cervical length of >25mm with a negative phIGFBP-1 test in a symptomatic patient indicates a low risk of preterm delivery and may therefore allow avoidance of unnecessary therapies. 15 NPV for predicting the risk of pre-term delivery was increased on combining FFN assessment to cervical length measurements in present study also ( Table 3) similar to that of Audibert F et al 8 In asymptomatic high risk group both FFN and phIGFBP-1 tests were found to have poor sensitivity and PPV; however NPV of the tests were high. Cervical length in this group also had poor accuracy to predict preterm birth.…”
Section: Discussionsupporting
confidence: 85%
“…However, Deplange et al [15] reported that the sensitivity, specificity, PPV and NPV of cervical length ≤ 20 mm were 75, 52, 21 and 92% for delivery before 34 weeks. Additionally, Paternoster et al [16] found that 26 mm was the best cut-off value for cervical length in terms of predicting preterm delivery with a sensitivity of 86.4%, specificity of 71.9%, PPV of 34.5% and NPV of 96.8%.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that two tests are independent, as shown by multivariate analysis. Paternoster et al [17] assessed both parameters in 201 patients with threatened preterm labor and determined cervical length cut off to be 26 mm with sensitivity, specificity, PPV and NPV of 86.4%, 71.9%, 34.5% and 96.8% respectively and having odds ratio of 16.18 (4.46-58.66). These parameters for phIGFBP-1 were 52.9%, 89.2%, 48.7% and 90.8% respectively with odds ratio of 9.29 (4.05-21.3).…”
Section: Discussionmentioning
confidence: 99%